1996
DOI: 10.1021/la960781a
|View full text |Cite
|
Sign up to set email alerts
|

Branched Fluorinated Nonionic Y-Shaped Surfactants. Effect of Molecular Geometry on Liquid Crystalline Phase Behavior

Abstract: The synthesis of branched partially fluorinated nonionic Y-shaped surfactants, with the general formula C F nC2N(EmM)2, where C F n denotes fluorinated alkyl chain F(CF2)n with n ) 4-10, C2 is C2H2, and EmM is oligooxyethylene monomethyl ether with m ) 2, 3, and their hydrocarbon analogs Cn+2N(EmM)2 (Cn equals hydrocarbon chain) is described. These surfactants are synthesized to analyze the influence of the fluorinated alkyl chain on the packing effects to amphiphilic layers in a binary surfactant/water system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…Like conventional nonionic surfactants such as poly(oxyethylene), perfluorosurfactants also show a rich phase behavior in aqueous solutions [21][22][23][24][25]. These surfactants in aqueous solution show an upper miscibility gap with a lower critical point in the temperature-composition diagram.…”
Section: Introductionmentioning
confidence: 99%
“…Like conventional nonionic surfactants such as poly(oxyethylene), perfluorosurfactants also show a rich phase behavior in aqueous solutions [21][22][23][24][25]. These surfactants in aqueous solution show an upper miscibility gap with a lower critical point in the temperature-composition diagram.…”
Section: Introductionmentioning
confidence: 99%
“…Monduzzi et al reported the counterion effect on the phase behavior of perfluropolyether carboxylates in water [12][13][14]. In spite of the growing study of phase behavior of nonionic fluorinated surfactants in water [15][16][17][18][19][20], the incorporation of fluorinated oil into self-organized structures of fluorocarbon surfactant has rarely been considered [21]. Perfluoropolyether (PFPE) oils have been used as lubricants in many industrial applications and possess the main properties of fluorinated surfactants like thermal, chemical, and biological inertness, and low compatibility with aqueous and hydrocarbon based systems.…”
Section: Introductionmentioning
confidence: 99%
“…The phase science of the mixture systems of this type of surfactant and water has so far been a problem attracting considerable attention in fundamental colloid science and the practical application of the surfactants (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The highly viscous mesomorphic phases is unfavorable to transport the surfactant preparations in the industrial production process.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is of critical importance to avoid the occurrence of the mesomorphic phases in the manufacture of the surfactant preparations. In the theoretical point of view, the potentially possible sequence of the mesophases appearing with the increase in water content in the mixture, I 2 (reversed discontinuous-type cubic)-H 2 (reversed hexagonal)-V 2 (reversed bicontinuoustype cubic)-L ␣ (lamellar)-V 1 (normal bicontinuous-type cubic)-H 1 (normal hexagonal)-I 1 (normal discontinuous-type cubic), has been interpreted in terms of order-disorder transition and shape transition (7,(11)(12)(13). The former is related to the requirement for the arrangement of the surfactant aggregates in the mixture systems arising from the excluded volume effect.…”
Section: Introductionmentioning
confidence: 99%